Use of a dual reporter plasmid to demonstrate bactofection with an attenuated AroA- derivative of Pasteurella multocida B:2 - Othman, Sarah; Roe, Andrew J.; Parton, Roger; Coote, John G. (Public Library of Science, 2013)
A reporter plasmid pSRG has been developed which expresses red fluorescent protein (RFP) from a constitutive prokaryotic promoter within Pasteurella multocida B:2 and green fluorescent protein (GFP) from a constitutive eukaryotic promoter within mammalian cells. This construct has been used to determine the location and viability of the bacteria when moving from the extracellular environment into the intracellular compartment of mammalian cells. Invasion assays with embryonic bovine lung (EBL) cells and an attenuated AroA- derivative of Pasteurella multocida B:2 (strain JRMT12), harbouring the plasmid pSRG, showed that RFP-expressing bacteria could be detected intracellularly at 3 h post-invasion. At this stage, some EBL cells harbouring RFP-expressing bacteria were observed to express GFP simultaneously, indicating release of the plasmid into the intracellular environment. At 5 h post-invasion, more EBL cells were expressing GFP, while still harbouring RFP-expressing bacteria. Concurrently, some EBL cells were shown to express only GFP, indicating loss of viable bacteria within these cells. These experiments proved the functionality of the pSRG dual reporter system and the potential of P. multocida B:2 JRMT12 for bactofection and delivery of a DNA vaccine.